2014
DOI: 10.1186/1471-2296-15-50
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner teachers’ job satisfaction and their medical students' wish to join the field – a correlational study

Abstract: BackgroundThere will be increasing competition for young physicians worldwide as more and more physicians retire. While enthusiasm towards GP work is important for GP teachers as role models, satisfaction within the profession has declined. This study aims to determine if medical students’ desire to become GPs is related to the job satisfaction of their teaching GPs and explore the factors tied to this job satisfaction.MethodsIn this cross-sectional, correlational study, teaching GPs of the University of Bern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Accordingly, our initial results largely confirm those of publications of overview character which describe experiences from similar educational projects with peer group character [10], [15]. A current German cross-sectional survey showed similar effects favouring a general practitioner's career path as a result of taking part in general medical educational projects [20].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Accordingly, our initial results largely confirm those of publications of overview character which describe experiences from similar educational projects with peer group character [10], [15]. A current German cross-sectional survey showed similar effects favouring a general practitioner's career path as a result of taking part in general medical educational projects [20].…”
Section: Discussionsupporting
confidence: 84%
“…The strong correlations between the students' (subsequent) preference for a general practitioner career path and the commitment of the lecturers, as well as the intensity of support and the interaction management in the project once again support the interpretation that a positive role model by the mentors is largely responsible for this [10], [15]. Currently ongoing international studies show that, in spite of positive educational benefits, even elaborately designed and realised curricular interventions have less influence upon the choice of medical specialty and the location of a practice than personal “practical experiences” [16], [17].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…16 Wright and Carrese's 17 work on role modeling found that potential role models must meet a certain level of clinical skill and demonstrate good verbal and nonverbal behavior, which are often prerequisites to being a department chair. Evidence that both residents and faculty view chairs as role models comes from a study that asked faculty to identify colleagues who were "clinically excellent" and residents to identify which faculty were role models.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although many aspects of GP job satisfaction are beyond the remit of medical schools, they can at least ensure that GP teachers are properly supported. An optional teaching qualification could open up a career path into academia for experienced GPs.…”
Section: Adequate Funding and Support Of Student Placements In Generamentioning
confidence: 99%